Review and Taxonomic Notes on the Genus Derostenus (Hymenoptera, Eulophidae) - Gumovsky, A.V. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
The genus Derostenus Westwood, 1833, is reviewed. 7 species are recognized for the genus, 2 of them described for a first time. These are: D. gemmeus Westwood (European), D. punctiscuta Thomson (European), D. freemani Yoshimoto (Nearctic), D. persicus sp. n. (Iran), D. trjapitzini sp. n. (described from the Russian Far-East), D. sulciscuta Hansson (Oriental, East Palearctic) and D. japonicus Hansson (Japan). The list of apomorphies of the genus Derostenus is supplemented by two characters: the anterior margin of each notaulus marked off by a drop-shape fissure, and the lateral panel of pronotum with a protruding flange. This flange is present as a stub-like process near the notaular fissure in the representatives of the gemmeus group, but being present as a plica in the sulciscuta group. Also, the representatives of the sulciscuta group have the dense brush of setae just in front of the notaular fissure. D. gemmeus recorded for a first time in Ukraine, D. sulciscuta recorded for a first time in the Russian Far-East (Primorye) and Kuril Archipelago, D. freemani recorded for a first time in Wisconsin state (USA). Table of characters distinguishing each species, is given.